People with intelectual disabilites: sex education needs and psychosexual problems - Σιαπέρας, Παναγιώτης; Σούλης, Σπυρίδων - Γεώργιος (Psychology: the Journal of the Hellenic Psychological Society, 2020)
Today even after the general progress based on Normalisation (Nirje, 1972), on services and policy for people with intellectual disabilities there is lack of knowledge and programmes on psychosexual issues they face. This paper tries to summarise and discuss the need for ordinary sexual life for people with intellectual disabilities. It presents the importance of programmes in sex education and contraception and how they should be introduced by the services. Furthermore it shows possible aetiology and impact of sexual abuse for the victim with intellectual disabilities and his/her family. Also it is presented how services should react and what kind of programmes should be introduced in cases of people with intellectual disabilities who either are victims of sexual abuse or commit sexual offence.